Asalib Taallum al-Muallimy al-Dirasat al-Islamiyah Fi al-Dirasat al-Ulya - Nuril Mufidah; Nur Kholis (AJIS: Academic Journal of Islamic Studies, 2019)
This study describes and identifies the learning styles of teachers who are undergoing a postgraduate course in Islamic studies. Using the quantitative descriptive method, with 27 subjects in the research subject, there is a second semester of the academic year 20018/2019 postgraduate program at Raden Rahmat Islamic University Malang, Indonesia. Data collection techniques used in this study were observation, interview, and documentation. The interview used was designed with limited answers. The results showed that 100% of students use information technology (such as Google search engines) to do tasks. 63.6% of students preferred to use book references and 36.4% preferred to search the internet. The learning media that are the choice of students are 54.5% in the form of textbooks, 27, 3% videos, and 18.2% power points. 54, 5% of students read books every day, 27, 3% when doing assignments and 18.2% once a week. With interest in the high reference book; 90.9% of students chose to enjoy learning to use social media and e-learning, and only 9.1% did not like it.